12 - The Reformed Agrarian Structure and Changing Dynamics of Rural Labour Migration in Zimbabwe - Chambati, Walter (Africa Development, 2022)
This article examines the changing dynamics of rural labour migration in Zimbabwe following the radical land redistribution since 2000 through the Fast Track Land Reform Programme (FTLRP). Since the colonial period, dispossessed peasants with inadequate land access were forced to offer cheap migrant wage labour for large-scale capitalist farms (LSCFs) and beyond. Despite the wide acknowledgement of the redistributive nature of the FTLRP, there is sparse understanding of how the new land access patterns impacted on rural labour migration. Empirical evidence from Goromonzi and Kwekwe districts demonstrates that while there were many peasant beneficiaries, land shortages were not completely eradicated and the new farm labour markets depended on the super-exploitation of landless migrants. Altogether, the data contradicts the conventional wisdom that views migration as a deliberate diversification strategy of household labour to enhance a livelihood. Rather, resistance to proletarianisation undergirds the struggles of farm labourers as they largely seek autonomous land-based social reproduction outside the wage economy.